The Combination of Socio-Political and Economic Criteria in Liberal Democratic Ideas - Shodmankulova Mubarak Mahamatkulovna (Genius Journals, 2023)
The article analyzes the process of development of the liberal worldview and political practice, reveals the main ideas of Constitutional priority-constitutionalism. In the conditions of liberal democracy, the Constitution is justified as one of the guarantees of the demand by society, the manifestation of the political, legal and economic capabilities of the individual. The features of the development of constitutionalism in Uzbekistan were analyzed as such characteristic forces as democratic modernization, national accord, independence.
Keywords: liberalism; Constitution; democracy; democratic modernization